The violation of the human rights of indigenous peoples: The case of the Unipacuyacu native community - Hallazi Méndez, Luis Alberto (2022)
In Peru, there are fifty-one indigenous peoples recognized by the Peruvian State, one of which is the Kakataibo people, located between the Huanuco and Ucayali regions, which includes eight native Kakataibo communities, which have been threatened by third party invasions of their recognized and titled territories. However, the native community of Unipacuyacu still does not have a property title, fact that has produced more aggressive invasions of their territory, to the point that their indigenous leaders have been threatened and their community leader, Arbildo Meléndez, was murdered. The national and international norms have been reviewed, as well as the minimum standards of international law for indigenous peoples, where the Unipacuyacu case is analyzed in the light of these norms and the new public policies for the protection of human rights defenders.